2018
DOI: 10.1155/2018/4251408
|View full text |Cite
|
Sign up to set email alerts
|

Positive Seatbelt Sign with Avulsed Leiomyoma following Motor Vehicle Accident Leading to Hemoperitoneum

Abstract: A positive seatbelt sign following a motor vehicle accident is associated with an increased risk of intra-abdominal injury and hemoperitoneum. Injury to the uterus in reproductive-age women can also occur. In this report, we describe a 29-year-old nulligravida female who presented to the emergency room following a motor vehicle accident at freeway speeds. A positive seatbelt sign was noted, and a focused assessment with sonography for trauma revealed hemoperitoneum with an incidental finding of uterine leiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The “submarine effect” refers to the sinking of the patient's body in the forward direction due to the impact of collision even if the seatbelt is properly attached to the ilium, causing the seatbelt to deviate upward and directly compress the abdominal organs ( Fig. 3 ) [5] , [6] . The abdominal wall and gastrointestinal tract have been reported to be injured because of the submarine effect owing to their position with respect to the seat belt, but in women, the risk of injury to the uterus must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The “submarine effect” refers to the sinking of the patient's body in the forward direction due to the impact of collision even if the seatbelt is properly attached to the ilium, causing the seatbelt to deviate upward and directly compress the abdominal organs ( Fig. 3 ) [5] , [6] . The abdominal wall and gastrointestinal tract have been reported to be injured because of the submarine effect owing to their position with respect to the seat belt, but in women, the risk of injury to the uterus must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 There are few case reports of traumatic avulsions of fibroids that result in a free-floating mass in the peritoneum. [7][8][9] It is thought that the mechanism of avulsion involves sheer stress from the uterus and fibroid moving at relatively different rates. 8 Manoukian et al 7 theorized that fibroids extending superior to the pubic rami are at a greater risk for trauma.…”
Section: Traumatic Avulsion Of a Uterine Fibroid After A Motor Vehicle Collisionmentioning
confidence: 99%
“…[7][8][9] It is thought that the mechanism of avulsion involves sheer stress from the uterus and fibroid moving at relatively different rates. 8 Manoukian et al 7 theorized that fibroids extending superior to the pubic rami are at a greater risk for trauma. This theory is further supported by the association of a pelvic fracture with traumatic avulsion of a uterine fibroid reported by Venables et al 8 Although it has been reported that a fibroid larger than 10 cm is a risk factor for spontaneous rupture of superficial vessels leading to hemorrhage, there are not sufficient reports of traumatic avulsion to definitively classify size as a risk factor.…”
Section: Traumatic Avulsion Of a Uterine Fibroid After A Motor Vehicle Collisionmentioning
confidence: 99%
See 1 more Smart Citation